Are businesses getting complacent when it comes to DDoS mitigation?. Issue 6 (June 2018) - Townsley, Chris
Abstract : There is no doubt that the number of distributed denial of service (DDoS) attacks is growing, as is the likelihood of any given organisation being attacked. DDoS attacks continue to grab headlines as they become more prevalent and more crippling in their effect. There is now a growing realisation among businesses that no industry is safe: any type of business with an online presence is at risk. The number of distributed denial of service (DDoS) attacks is growing, as is the likelihood of any given organisation being attacked. There is now a growing realisation among businesses that no industry is safe: any type of business with an online presence is at risk. And yet still we hear the phrase 'it will never happen to me'. Too few organisations are taking note of the multiple warnings in the media and from the security industry, warns Chris Townsley of CDNetworks.